An Application-Level QoS Control Method Based on Local Bandwidth Scheduling. (6th June 2018) - Wang, Yong; Xu, Fu; Chen, Zhibo; Sun, Yu; Zhang, Haiyan
Abstract : Quality of service (QoS) is an important performance indicator for Web applications and bandwidth is a key factor affecting QoS. Current methods use network protocols or ports to schedule bandwidth, which require tedious manual configurations or modifications of the underlying network. Some applications use dynamic ports and the traditional port-based bandwidth control methods cannot deal with them. A new QoS control method based on local bandwidth scheduling is proposed, which can schedule bandwidth at application level in a user-transparent way and it does not require tedious manual configurations. Experimental results indicate that the new method can effectively improve the QoS for applications, and it can be easily integrated into current Web applications without the need to modify the underlying network.